An ultra-high performance concrete added with an ultra-sulfated cement and a method for preparing the same

CN122667893APending Publication Date: 2026-09-01JIANGSU JIANYUAN BUILDING MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610745413.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0003]然而,超硫酸盐水泥存在早期强度发展缓慢、抗碳化性能差等固有缺陷,严重限制了其在超高性能混凝土中的推广应用

Benefits of technology

本发明将预碳化γ-硅酸二钙、CO2纳米气泡水与浆料混合,以实现抗碳化、高抗压强度及优异的早期强度的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to an ultra-high performance concrete with added supersulfate cement and its preparation method, belonging to the field of concrete technology. This invention uses granulated blast furnace slag powder, desulfurized gypsum, and cement clinker as the supersulfate cement matrix, and introduces pre-carbonized dicalcium γ-silicate, CO2 nanobubble water, and triethanolamine as ternary synergistic components. The finished product is obtained through early sealed in-situ carbonization-hydration synergistic curing supplemented by standard curing. Pre-carbonized dicalcium γ-silicate provides heterogeneous nucleation sites to accelerate early hydration; CO2 nanobubbles achieve in-situ carbonization filling submicron pores; triethanolamine simultaneously enhances the carbonization and hydration reaction rates; and sealed curing protects hydration products from decalcification. Through multi-level synergistic effects, this invention significantly improves the early strength, compressive strength, and carbonation resistance of concrete. The concrete prepared by this invention exhibits carbonation resistance, high compressive strength, and excellent early strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete technology, specifically to an ultra-high performance concrete with added supersulfate cement and its preparation method. Background Technology

[0002] As a low-carbon cementitious material, supersulfate cement can dispose of large quantities of industrial solid waste such as granulated blast furnace slag and desulfurized gypsum. Compared with ordinary silicate cement, it can reduce carbon emissions by about 70%, and has important application value in the fields of green building and sustainable development.

[0003] However, hypersulfate cement suffers from inherent drawbacks such as slow early strength development and poor carbonation resistance, severely limiting its widespread application in ultra-high performance concrete. Existing technologies often improve performance by increasing the clinker content or adding a single admixture; however, the former weakens its low-carbon advantage, while the latter struggles to simultaneously address the conflict between early strength and carbonation resistance. Furthermore, traditional carbonation curing processes easily lead to decalcification and decomposition of hydration products, which in turn reduces the later-stage strength and durability of the concrete. Therefore, developing a green preparation technology that can simultaneously improve the early strength and carbonation resistance of hypersulfate cement-based concrete has become a critical technical problem urgently needing to be solved in this field. Summary of the Invention

[0004] The purpose of this invention is to provide an ultra-high performance concrete with added supersulfate cement and its preparation method, so as to solve the problems existing in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing ultra-high performance concrete with added supersulfate cement, comprising the following steps: (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, anhydrous ethanol was added and ball milled at a ball-to-material ratio of 6:1 for 3 hours. The mixture was dried at 60°C for 12 hours, sieved and pressed into tablets to obtain round tablets. Microwave sintering was performed by heating to 800°C at a heating rate of 5°C / min and holding for 30 minutes. The temperature was then increased to 1350°C and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace. After ball milling for 40 minutes, the mixture was sieved to obtain the self-made γ-dicalcium silicate powder. (2) Mix the self-made γ-dicalcium silicate powder with CO2 nanobubble water prepared by microporous membrane diffusion at a mass ratio of 1:1.5~2.5, stir for 45 min at room temperature in a sealed environment to obtain pre-carbonized γ-dicalcium silicate slurry; (3) Mix 50-70 parts by weight of granulated blast furnace slag powder, 5-10 parts by weight of fly ash, 5-10 parts by weight of ordinary silicate cement and 10-20 parts by weight of desulfurized gypsum, then add mixed aggregate with a sand-to-binder ratio of 1.0, and dry mix at room temperature for 5 minutes; then add CO2 nano-bubble water with a water-to-binder ratio of 0.38, 10-20 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of water-reducing agent and 0.05 parts by weight of catalyst, and wet mix for 2 minutes to obtain ultra-high performance concrete.

[0006] Furthermore, the self-made γ-dicalcium silicate powder mentioned in step (1) is: self-made γ-dicalcium silicate powder that has passed through a 200-mesh standard sieve.

[0007] Furthermore, the CO2 nanobubble water mentioned in step (2) is: CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm.

[0008] Furthermore, the granulated blast furnace slag powder mentioned in step (3) is: S95 grade granulated blast furnace slag powder.

[0009] Furthermore, the silicate cement mentioned in step (3) is ordinary silicate cement of P·I52.5.

[0010] Furthermore, the desulfurized gypsum in step (3) is: desulfurized gypsum with a calcium sulfate dihydrate content ≥85%.

[0011] Furthermore, the mixed aggregate in step (3) is prepared by mixing 50-mesh quartz sand and 100-mesh quartz sand at a mass ratio of 6:4.

[0012] Furthermore, the water-reducing agent mentioned in step (3) is a powdered polycarboxylate water-reducing agent with an effective content of ≥98%.

[0013] Furthermore, the catalyst in step (3) is triethanolamine.

[0014] Furthermore, in the application of ultra-high performance concrete with added supersulfate cement, the ultra-high performance concrete is poured into a 100mm cube standard mold, vibrated on a vibrating table for 15 seconds to ensure full compaction, and immediately after molding, the surface of the specimen is tightly covered with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss, and sealed for curing for 24 hours, maintaining a standard curing room temperature of 20℃ and a relative humidity ≥95%; after the sealed curing is completed, the mold and plastic film are removed, and the specimen is placed in a standard curing room for continued curing until the specified age.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention mixes pre-carbonized dicalcium γ-silicate, CO2 nanobubble water with slurry to achieve the effects of anti-carbonation, high compressive strength and excellent early strength.

[0016] This invention uses granulated blast furnace slag powder, desulfurized gypsum, and cement clinker as the supersulfate cement matrix, and employs pre-carbonized dicalcium silicate, CO2 nanobubble water, and triethanolamine as ternary synergistic components. After early-stage sealed in-situ carbonation-hydration synergistic curing, supplemented by standard curing, ultra-high performance concrete is obtained. During the pre-carbonation treatment, dicalcium silicate preferentially forms a nano-calcium carbonate coating layer on its surface, providing numerous heterogeneous nucleation sites for ettringite and C-(A)-SH gel, accelerating the early hydration process. CO2 nanobubbles are uniformly dispersed within the slurry, achieving in-situ carbonation. The CO2 released by the bursting of nanobubbles reacts with calcium ions in the matrix to form nano-calcium carbonate, filling submicron-level pores and significantly improving the matrix density. Triethanolamine acts as a CO2 hydration catalyst and calcium ion complexing agent, accelerating... CO2 converts to carbonate and promotes the dissolution of calcium ions in slag, thus simultaneously increasing the carbonation-hydration reaction rate. Under sealed conditions, in-situ carbonation-hydration synergistic curing maintains the partial pressure of CO2 in the system, allowing dicalcium γ-silicate to preferentially react with invading CO2 to form calcium carbonate and amorphous silica gel. This consumes CO2 and protects C-(A)-SH gel and ettringite from decalcification and carbonation damage. The above synergy significantly improves the early strength and carbonation resistance of the material. At the same time, the nano-calcium carbonate seeds introduced by pre-carbonation induce uniform nucleation and growth of ettringite. The calcium carbonate formed by in-situ mineralization of CO2 nanobubbles fills the capillary pores and interface transition zone. The continuous hydration promoted by triethanolamine allows the C-(A)-SH gel to fully develop. The above multi-level synergy significantly improves the compressive strength and carbonation resistance of concrete simultaneously. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The test methods for various indicators of the ultra-high performance concrete with added supersulfate cement prepared in the following embodiments are as follows: Early strength and compressive strength tests: The concrete prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested according to the national standard GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The compressive strength at 1d, 3d, 7d and 28d was recorded.

[0019] Carbonation resistance test: The carbonation depth of the concrete prepared in Examples 1 to 5 and Comparative Examples 1 to 6 was obtained after curing for 28 days according to GB / T 42277-2022 "Test method for carbonation of cement mortar". Example 1

[0020] (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, and anhydrous ethanol was added as the ball milling medium for ball milling. The ball-to-material ratio was 6:1. The mixture was ball milled at 350 rpm for 3 hours, dried at 60℃ for 12 hours, and passed through a 200-mesh standard sieve. The mixture was then pressed into tablets at a pressure of 12 MPa and held for 45 seconds to obtain φ25 mm × 6 mm round tablets. Microwave sintering was performed by heating to 800℃ at a heating rate of 5℃ / min and holding for 30 minutes. The temperature was then further increased to 1350℃ and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace to obtain γ-dicalcium silicate blocks. Slow cooling was used to ensure that the β→γ crystal transformation was fully completed. The mixture was then dry-milled in a planetary ball mill for 40 minutes and passed through a 200-mesh square hole sieve to obtain homemade γ-dicalcium silicate powder. (2) CO2 nanobubble water was prepared by microporous membrane diffusion method. The liquid phase pressure was adjusted to 150 kPa, and the circulation was stable for 3 min to remove the gas bubbles in the pipeline. The gas valve was slowly opened and the gas phase pressure was adjusted to 0.3 MPa. CO2 gas penetrated the 50 nm ceramic membrane pores under a pressure difference of 0.3 MPa and formed nanobubbles in the water phase inside the membrane. The water flow shear force caused the bubbles to detach from the membrane surface and disperse evenly. The gas-liquid ratio was controlled to be 2.87%. The CO2 gas flow rate and the circulating water flow rate were adjusted according to this ratio. The system was kept running continuously for 30 min and circulated 3 times to fully dissolve CO2 and form CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm. It was stored in the refrigerator below 4℃. (3) Mix the self-made γ-dicalcium silicate powder with CO2 nano bubble water at a mass ratio of 1:1.5, stir at 200 rpm for 45 min under room temperature and sealed conditions to complete the pre-carbonization pretreatment of γ-dicalcium silicate and obtain pre-carbonized γ-dicalcium silicate slurry. (4) Mix 50 parts by weight of S95 grade granulated blast furnace slag powder, 5 parts by weight of grade 1 fly ash, 5 parts by weight of P·I52.5 ordinary Portland cement and 10 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85%, and then add mixed aggregate with a sand-to-binder ratio of 1.0. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. Dry mix at 100 rpm for 5 min at room temperature; then add CO2 nano bubble water with a water-to-binder ratio of 0.38, 10 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine, and wet mix at 300 rpm for 2 min to obtain ultra-high performance concrete. (5) Pour the ultra-high performance concrete into a 100mm cube standard mold, vibrate it on a vibrating table for 15s to make it fully compacted, and immediately cover the surface of the specimen with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. Perform sealed curing for 24 hours, maintaining the standard curing room temperature at 20℃ and relative humidity ≥95%. After the sealed curing is completed, remove the mold and plastic film, and place it in the standard curing room to continue curing until the specified age. Example 2

[0021] (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, and anhydrous ethanol was added as the ball milling medium for ball milling. The ball-to-material ratio was 6:1. The mixture was ball milled at 350 rpm for 3 hours, dried at 60℃ for 12 hours, and passed through a 200-mesh standard sieve. The mixture was then pressed into tablets at a pressure of 12 MPa and held for 45 seconds to obtain φ25 mm × 6 mm round tablets. Microwave sintering was performed by heating to 800℃ at a heating rate of 5℃ / min and holding for 30 minutes. The temperature was then further increased to 1350℃ and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace to obtain γ-dicalcium silicate blocks. Slow cooling was used to ensure that the β→γ crystal transformation was fully completed. The mixture was then dry-milled in a planetary ball mill for 40 minutes and passed through a 200-mesh square hole sieve to obtain homemade γ-dicalcium silicate powder. (2) CO2 nanobubble water was prepared by microporous membrane diffusion method. The liquid phase pressure was adjusted to 150 kPa, and the circulation was stable for 3 min to remove the gas bubbles in the pipeline. The gas valve was slowly opened and the gas phase pressure was adjusted to 0.3 MPa. CO2 gas penetrated the 50 nm ceramic membrane pores under a pressure difference of 0.3 MPa and formed nanobubbles in the water phase inside the membrane. The water flow shear force caused the bubbles to detach from the membrane surface and disperse evenly. The gas-liquid ratio was controlled to be 2.87%. The CO2 gas flow rate and the circulating water flow rate were adjusted according to this ratio. The system was kept running continuously for 30 min and circulated 3 times to fully dissolve CO2 and form CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm. It was stored in the refrigerator below 4℃. (3) Mix the self-made γ-dicalcium silicate powder with CO2 nano bubble water at a mass ratio of 1:1.8, stir at 200 rpm for 45 min under room temperature and sealed conditions to complete the pre-carbonization pretreatment of γ-dicalcium silicate and obtain pre-carbonized γ-dicalcium silicate slurry. (4) Mix 55 parts by weight of S95 grade granulated blast furnace slag powder, 6 parts by weight of grade 1 fly ash, 6 parts by weight of P·I52.5 ordinary Portland cement and 13 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85%, and then add mixed aggregate with a sand-to-binder ratio of 1.0. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. Dry mix at 100 rpm for 5 min at room temperature; then add CO2 nano bubble water with a water-to-binder ratio of 0.38, 13 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine, and wet mix at 300 rpm for 2 min to obtain ultra-high performance concrete. (5) Pour the ultra-high performance concrete into a 100mm cube standard mold, vibrate it on a vibrating table for 15s to make it fully compacted, and immediately cover the surface of the specimen with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. Perform sealed curing for 24 hours, maintaining the standard curing room temperature at 20℃ and relative humidity ≥95%. After the sealed curing is completed, remove the mold and plastic film, and place it in the standard curing room to continue curing until the specified age. Example 3

[0022] (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, and anhydrous ethanol was added as the ball milling medium for ball milling. The ball-to-material ratio was 6:1. The mixture was ball milled at 350 rpm for 3 hours, dried at 60℃ for 12 hours, and passed through a 200-mesh standard sieve. The mixture was then pressed into tablets at a pressure of 12 MPa and held for 45 seconds to obtain φ25 mm × 6 mm round tablets. Microwave sintering was performed by heating to 800℃ at a heating rate of 5℃ / min and holding for 30 minutes. The temperature was then further increased to 1350℃ and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace to obtain γ-dicalcium silicate blocks. Slow cooling was used to ensure that the β→γ crystal transformation was fully completed. The mixture was then dry-milled in a planetary ball mill for 40 minutes and passed through a 200-mesh square hole sieve to obtain homemade γ-dicalcium silicate powder. (2) CO2 nanobubble water was prepared by microporous membrane diffusion method. The liquid phase pressure was adjusted to 150 kPa, and the circulation was stable for 3 min to remove the gas bubbles in the pipeline. The gas valve was slowly opened and the gas phase pressure was adjusted to 0.3 MPa. CO2 gas penetrated the 50 nm ceramic membrane pores under a pressure difference of 0.3 MPa and formed nanobubbles in the water phase inside the membrane. The water flow shear force caused the bubbles to detach from the membrane surface and disperse evenly. The gas-liquid ratio was controlled to be 2.87%. The CO2 gas flow rate and the circulating water flow rate were adjusted according to this ratio. The system was kept running continuously for 30 min and circulated 3 times to fully dissolve CO2 and form CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm. It was stored in the refrigerator below 4℃. (3) Mix the self-made γ-dicalcium silicate powder with CO2 nano bubble water at a mass ratio of 1:2, stir at 200 rpm for 45 min under room temperature and sealed conditions to complete the pre-carbonization pretreatment of γ-dicalcium silicate and obtain pre-carbonized γ-dicalcium silicate slurry. (4) Mix 60 parts by weight of S95 grade granulated blast furnace slag powder, 8 parts by weight of grade 1 fly ash, 8 parts by weight of P·I52.5 ordinary Portland cement and 15 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85%, and then add mixed aggregate with a sand-to-binder ratio of 1.0. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. Dry mix at 100 rpm for 5 min at room temperature; then add CO2 nano bubble water with a water-to-binder ratio of 0.38, 15 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine, and wet mix at 300 rpm for 2 min to obtain ultra-high performance concrete. (5) Pour the ultra-high performance concrete into a 100mm cube standard mold, vibrate it on a vibrating table for 15s to make it fully compacted, and immediately cover the surface of the specimen with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. Perform sealed curing for 24 hours, maintaining the standard curing room temperature at 20℃ and relative humidity ≥95%. After the sealed curing is completed, remove the mold and plastic film, and place it in the standard curing room to continue curing until the specified age. Example 4

[0023] (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, and anhydrous ethanol was added as the ball milling medium for ball milling. The ball-to-material ratio was 6:1. The mixture was ball milled at 350 rpm for 3 hours, dried at 60℃ for 12 hours, and passed through a 200-mesh standard sieve. The mixture was then pressed into tablets at a pressure of 12 MPa and held for 45 seconds to obtain φ25 mm × 6 mm round tablets. Microwave sintering was performed by heating to 800℃ at a heating rate of 5℃ / min and holding for 30 minutes. The temperature was then further increased to 1350℃ and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace to obtain γ-dicalcium silicate blocks. Slow cooling was used to ensure that the β→γ crystal transformation was fully completed. The mixture was then dry-milled in a planetary ball mill for 40 minutes and passed through a 200-mesh square hole sieve to obtain homemade γ-dicalcium silicate powder. (2) CO2 nanobubble water was prepared by microporous membrane diffusion method. The liquid phase pressure was adjusted to 150 kPa, and the circulation was stable for 3 min to remove the gas bubbles in the pipeline. The gas valve was slowly opened and the gas phase pressure was adjusted to 0.3 MPa. CO2 gas penetrated the 50 nm ceramic membrane pores under a pressure difference of 0.3 MPa and formed nanobubbles in the water phase inside the membrane. The water flow shear force caused the bubbles to detach from the membrane surface and disperse evenly. The gas-liquid ratio was controlled to be 2.87%. The CO2 gas flow rate and the circulating water flow rate were adjusted according to this ratio. The system was kept running continuously for 30 min and circulated 3 times to fully dissolve CO2 and form CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm. It was stored in the refrigerator below 4℃. (3) Mix the self-made γ-dicalcium silicate powder with CO2 nano bubble water at a mass ratio of 1:2.2, stir at 200 rpm for 45 min under room temperature and sealed conditions to complete the pre-carbonization pretreatment of γ-dicalcium silicate and obtain pre-carbonized γ-dicalcium silicate slurry. (4) Mix 65 parts by weight of S95 grade granulated blast furnace slag powder, 9 parts by weight of grade 1 fly ash, 9 parts by weight of P·I52.5 ordinary Portland cement and 18 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85%, and then add mixed aggregate with a sand-to-binder ratio of 1.0. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. Dry mix at 100 rpm for 5 min at room temperature; then add CO2 nano bubble water with a water-to-binder ratio of 0.38, 18 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine, and wet mix at 300 rpm for 2 min to obtain ultra-high performance concrete. (5) Pour the ultra-high performance concrete into a 100mm cube standard mold, vibrate it on a vibrating table for 15s to make it fully compacted, and immediately cover the surface of the specimen with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. Perform sealed curing for 24 hours, maintaining the standard curing room temperature at 20℃ and relative humidity ≥95%. After the sealed curing is completed, remove the mold and plastic film, and place it in the standard curing room to continue curing until the specified age. Example 5

[0024] (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, and anhydrous ethanol was added as the ball milling medium for ball milling. The ball-to-material ratio was 6:1. The mixture was ball milled at 350 rpm for 3 hours, dried at 60℃ for 12 hours, and passed through a 200-mesh standard sieve. The mixture was then pressed into tablets at a pressure of 12 MPa and held for 45 seconds to obtain φ25 mm × 6 mm round tablets. Microwave sintering was performed by heating to 800℃ at a heating rate of 5℃ / min and holding for 30 minutes. The temperature was then further increased to 1350℃ and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace to obtain γ-dicalcium silicate blocks. Slow cooling was used to ensure that the β→γ crystal transformation was fully completed. The mixture was then dry-milled in a planetary ball mill for 40 minutes and passed through a 200-mesh square hole sieve to obtain homemade γ-dicalcium silicate powder. (2) CO2 nanobubble water was prepared by microporous membrane diffusion method. The liquid phase pressure was adjusted to 150 kPa, and the circulation was stable for 3 min to remove the gas bubbles in the pipeline. The gas valve was slowly opened and the gas phase pressure was adjusted to 0.3 MPa. CO2 gas penetrated the 50 nm ceramic membrane pores under a pressure difference of 0.3 MPa and formed nanobubbles in the water phase inside the membrane. The water flow shear force caused the bubbles to detach from the membrane surface and disperse evenly. The gas-liquid ratio was controlled to be 2.87%. The CO2 gas flow rate and the circulating water flow rate were adjusted according to this ratio. The system was kept running continuously for 30 min and circulated 3 times to fully dissolve CO2 and form CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm. It was stored in the refrigerator below 4℃. (3) Mix the self-made γ-dicalcium silicate powder with CO2 nano bubble water at a mass ratio of 1:2.5, stir at 200 rpm for 45 min under room temperature and sealed conditions to complete the pre-carbonization pretreatment of γ-dicalcium silicate and obtain pre-carbonized γ-dicalcium silicate slurry. (4) Mix 70 parts by weight of S95 grade granulated blast furnace slag powder, 10 parts by weight of grade 1 fly ash, 10 parts by weight of P·I52.5 ordinary Portland cement and 20 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85%, and then add mixed aggregate with a sand-to-binder ratio of 1.0. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. Dry mix at 100 rpm for 5 min at room temperature; then add CO2 nano bubble water with a water-to-binder ratio of 0.38, 20 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine, and wet mix at 300 rpm for 2 min to obtain ultra-high performance concrete. (5) Pour the ultra-high performance concrete into a 100mm cube standard mold, vibrate it on a vibrating table for 15s to make it fully compacted, and immediately cover the surface of the specimen with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. Perform sealed curing for 24 hours, maintaining the standard curing room temperature at 20℃ and relative humidity ≥95%. After the sealed curing is completed, remove the mold and plastic film, and place it in the standard curing room to continue curing until the specified age.

[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that Comparative Example 1 is a blank group, and conventional silicate cement is used for testing.

[0026] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that step (3) is omitted, and step (4) is changed to: 60 parts by weight of S95 grade granulated blast furnace slag powder, 8 parts by weight of grade 1 fly ash, 8 parts by weight of P·I52.5 ordinary silicate cement and 15 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85% are mixed, and then mixed aggregate with a sand-to-binder ratio of 1.0 is added. The mixed aggregate is prepared by mixing 50 mesh quartz sand and 100 mesh quartz sand at a mass ratio of 6:4. The mixture is dry-mixed at 100 rpm for 5 min at room temperature; then CO2 nano-bubble water with a water-to-binder ratio of 0.38, 15 parts by weight of self-made γ-dicalcium silicate powder, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine are added, and the mixture is wet-mixed at 300 rpm for 2 min to obtain ultra-high performance concrete. The remaining steps are the same as in Example 3.

[0027] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that steps (1) and (3) are omitted, and step (4) is changed to: 60 parts by weight of S95 grade granulated blast furnace slag powder, 8 parts by weight of grade 1 fly ash, 8 parts by weight of P·I52.5 ordinary silicate cement and 15 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85% are mixed, and then mixed aggregate with a sand-to-binder ratio of 1.0 is added. The mixed aggregate is prepared by mixing 50-mesh quartz sand and 100-mesh quartz sand at a mass ratio of 6:4. The mixture is dry-mixed at 100 rpm for 5 min at room temperature; then CO2 nano-bubble water with a water-to-binder ratio of 0.38, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine are added, and the mixture is wet-mixed at 300 rpm for 2 min to obtain ultra-high performance concrete. The remaining steps are the same as in Example 3.

[0028] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that triethanolamine is not added; the remaining steps are the same as in Example 3.

[0029] Comparative Example 5 The difference between Comparative Example 5 and Example 3 lies in step (4). Step (4) is changed to: 60 parts by weight of S95 grade granulated blast furnace slag powder, 8 parts by weight of grade 1 fly ash, 8 parts by weight of P·I52.5 ordinary silicate cement and 15 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85% are mixed, and then mixed aggregate with a sand-to-binder ratio of 1.0 is added. The mixed aggregate is prepared by mixing 50-mesh quartz sand and 100-mesh quartz sand at a mass ratio of 6:4. The mixture is dry-mixed at 100 rpm for 5 minutes at room temperature; then deionized water with a water-to-binder ratio of 0.38, 15 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine are added, and the mixture is wet-mixed at 300 rpm for 2 minutes to obtain ultra-high performance concrete. The remaining steps are the same as in Example 3.

[0030] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that steps (1), (2), and (3) are omitted, and step (4) is changed to: 60 parts by weight of S95 grade granulated blast furnace slag powder, 8 parts by weight of grade 1 fly ash, 8 parts by weight of P·I52.5 ordinary silicate cement and 15 parts by weight of desulfurized gypsum with calcium sulfate dihydrate content ≥85% are mixed, and then mixed aggregate with a sand-to-binder ratio of 1.0 is added. The mixed aggregate is prepared by mixing 50-mesh quartz sand and 100-mesh quartz sand at a mass ratio of 6:4. The mixture is dry-mixed at 100 rpm for 5 min at room temperature; then deionized water with a water-to-binder ratio of 0.38, 15 parts by weight of self-made γ-dicalcium silicate powder, 0.3 parts by weight of powdered polycarboxylate superplasticizer with an effective content ≥98% and 0.05 parts by weight of triethanolamine are added, and the mixture is wet-mixed at 300 rpm for 2 min to obtain ultra-high performance concrete. The remaining steps are the same as in Example 3.

[0031] Example of effect Table 1 below presents the performance analysis results of ultra-high performance concrete with added supersulfate cement according to Examples 1 to 5 and Comparative Examples 1 to 6 of the present invention.

[0032] Table 1

[0033]

[0034] A comparison of the experimental data on compressive strength between the examples and comparative examples reveals that this invention uses granulated blast furnace slag powder, desulfurized gypsum, and cement clinker as the supersulfate cement matrix, and employs pre-carbonized dicalcium silicate, CO2 nanobubble water, and triethanolamine as ternary synergistic components. After early-stage sealed in-situ carbonation-hydration synergistic curing, supplemented by standard curing, ultra-high performance concrete is obtained. During the pre-carbonation treatment, dicalcium silicate preferentially forms a nano-calcium carbonate coating layer on its surface, providing numerous heterogeneous nucleation sites for ettringite and C-(A)-SH gel, accelerating the early hydration process. CO2 nanobubbles are uniformly dispersed within the slurry, achieving in-situ carbonation. The CO2 released by the bursting of nanobubbles reacts with calcium ions in the matrix to form nano-calcium carbonate, filling submicron-level pores and significantly improving the matrix density. A comparison of the experimental data on carbonation depth between the examples and comparative examples reveals that this invention… In this invention, triethanolamine acts as a CO2 hydration catalyst and calcium ion complexing agent, accelerating the conversion of CO2 to carbonate and promoting the dissolution of calcium ions in slag, thereby simultaneously increasing the carbonation-hydration reaction rate. Under sealed conditions, in-situ carbonation-hydration synergistic curing maintains the partial pressure of CO2 within the system, allowing dicalcium γ-silicate to preferentially react with invading CO2 to form calcium carbonate and amorphous silica gel. This consumes CO2 and protects C-(A)-SH gel and ettringite from decalcification and carbonation damage. The above synergy significantly improves the early strength and carbonation resistance of the material. Simultaneously, the nano-calcium carbonate seeds introduced by pre-carbonation induce uniform nucleation and growth of ettringite, and the calcium carbonate formed by in-situ mineralization of CO2 nanobubbles fills the capillary pores and interfacial transition zone. The continuous hydration promoted by triethanolamine allows the C-(A)-SH gel to fully develop. The above multi-level synergy significantly improves the compressive strength and carbonation resistance of concrete simultaneously.

[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for preparing ultra-high performance concrete with added supersulfate cement, characterized in that, Includes the following steps: (1) Calcium carbonate and silicon dioxide were mixed at a mass ratio of 10:3, anhydrous ethanol was added and ball milled at a ball-to-material ratio of 6:1 for 3 hours. The mixture was dried at 60°C for 12 hours, sieved and pressed into tablets to obtain round tablets. Microwave sintering was performed by heating to 800°C at a heating rate of 5°C / min and holding for 30 minutes. The temperature was then increased to 1350°C and held for 120 minutes. The mixture was then allowed to cool slowly to room temperature in the furnace. After ball milling for 40 minutes, the mixture was sieved to obtain the self-made γ-dicalcium silicate powder. (2) Mix the self-made γ-dicalcium silicate powder with CO2 nanobubble water prepared by microporous membrane diffusion at a mass ratio of 1:1.5~2.5, stir for 45 min at room temperature in a sealed environment to obtain pre-carbonized γ-dicalcium silicate slurry; (3) Mix 50-70 parts by weight of granulated blast furnace slag powder, 5-10 parts by weight of fly ash, 5-10 parts by weight of ordinary silicate cement and 10-20 parts by weight of desulfurized gypsum, then add mixed aggregate with a sand-to-binder ratio of 1.0, and dry mix at room temperature for 5 minutes; then add CO2 nano-bubble water with a water-to-binder ratio of 0.38, 10-20 parts by weight of pre-carbonized γ-dicalcium silicate paste, 0.3 parts by weight of water-reducing agent and 0.05 parts by weight of catalyst, and wet mix for 2 minutes to obtain ultra-high performance concrete.

2. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The self-made γ-dicalcium silicate powder mentioned in step (1) is: self-made γ-dicalcium silicate powder that has passed through a 200-mesh standard sieve.

3. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The CO2 nanobubble water mentioned in step (2) is CO2 nanobubble water with a CO2 content of 8 mg / L and an average bubble particle size of 100 nm.

4. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The granulated blast furnace slag powder mentioned in step (3) is: S95 grade granulated blast furnace slag powder.

5. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The silicate cement mentioned in step (3) is ordinary silicate cement of P·I52.

5.

6. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The desulfurized gypsum in step (3) is: desulfurized gypsum with a calcium sulfate dihydrate content of ≥85%.

7. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The mixed aggregate mentioned in step (3) is prepared by mixing 50-mesh quartz sand and 100-mesh quartz sand at a mass ratio of 6:

4.

8. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The water-reducing agent mentioned in step (3) is a powdered polycarboxylate water-reducing agent with an effective content of ≥98%.

9. The ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, The catalyst mentioned in step (3) is triethanolamine.

10. The application of ultra-high performance concrete with added supersulfate cement according to claim 1, characterized in that, Ultra-high performance concrete was poured into a 100mm cube standard mold and vibrated on a vibrating table for 15 seconds to ensure full compaction. Immediately after molding, the surface of the specimen was tightly covered with a 0.1mm thick polyethylene plastic film to prevent moisture evaporation and CO2 loss. The specimen was then sealed and cured for 24 hours, maintaining a standard curing room temperature of 20℃ and a relative humidity of ≥95%. After the sealing curing was completed, the mold and plastic film were removed, and the specimen was placed in a standard curing room for continued curing until the specified age.